Marketing Analysis of Gasketed Plate Heat Exchangers using the SWOT Method and Analytic Network Process - Maulana, Danis; Fatimah, Ismi; Rachman, Farizi; Akseptori, Ristanti; Devi, Yesica Novrita (Fakultas Ekonomi dan Bisnis Universitas Samudra, 2026)
The research evaluates the marketing strategy for gasketed plate heat exchangers at PT. XYZ, a mechanical and electrical engineering service firm in Surabaya. A SWOT analysis maps strengths, weaknesses, opportunities, and threats, while the Analytic Network Process ranks interrelated marketing elements. Score place the company in Quadrant I of the grand strategy matrix, indicating an aggressive growth posture. Promotion receives the highest weight, followed by product, price, and distribution. Leading sub-criteria are informational advertising, discounts, and sales promotions. The findings show that information-centric promotion is the most effective lever for expanding market coverage and boosting PT. XYZ’s sales performance.